2011
DOI: 10.5194/cpd-7-3449-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial GDGTs in Holocene sediments and catchment soils of a high-alpine lake: application of the MBT/CBT-paleothermometer

Abstract: A novel proxy for continental mean annual air temperature (MAAT) and soil-pH, the MBT/CBT-paleothermometer, is based on the temperature (<i>T</i>) and pH-dependent distribution of specific bacterial membrane lipids (branched glycerol dialkyl glycerol tetraethers – GDGTs) in soil organic matter. Here, we tested the applicability of the MBT/CBT-paleothermometer to sediments from Lake Cadagno, a small high-alpine lake in southern Switzerland with a small catchment of 2.4 km<sup>2</sup>. We… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 80 publications
1
23
0
Order By: Relevance
“…Peterse et al, 2011), speleothems (Blyth and Schouten, 2013), lake sediments (e.g. Niemann et al, 2012), but initially in marine sediments (e.g. Weijers et al, 2007b;Bendle et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Peterse et al, 2011), speleothems (Blyth and Schouten, 2013), lake sediments (e.g. Niemann et al, 2012), but initially in marine sediments (e.g. Weijers et al, 2007b;Bendle et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The MBT/CBT index from terrestrial soils has subsequently been used to estimate paleotemperatures in marine sediment cores from coastal regions (Rueda et al, 2009;Weijers et al, 2007a), and potentially be additionally used to reconstruct the paleotemperature from lacustrine sediment cores (e.g. Tierney et al, 2010;Niemann et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies observed that branched GDGTs are ubiquitously found in lake sediments (e.g. Niemann et al, 2012;Sinninghe Damsté et al, 2009;Tierney et al, 2010;Tyler et al, 2010), numerous studies have found evidence suggesting that branched GDGTs in the many lake sediments were not only derived from the surrounding soils. Instead, at least part of the branched GDGTs appear to have been produced within the water column or sediments of these lakes (Bechtel et al, 2010;Loomis et al, 2011;Sinninghe Damsté et al, 2009;Tierney and Russell, 2009;Tierney et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Niemann et al 2012), differences in brGDGT distributions between lake sediments and adjacent terrestrial soils have now been observed at numerous sites, such as Lake Towuti, Indonesia (Tierney and Russell, 2009), several small lakes in western Uganda (Loomis et al, 2011), and a small pond in the US (Tierney et al, 2012). Using a relatively small soil dataset, Sinninghe reported this same discrepancy between soils and sediments at Lake Challa, and speculated that this may point to an additional source of brGDGTs either from outside the area then sampled for soils, or in the water column or sediments of Lake Challa, making it necessary to further constrain fluxes to the lake system.…”
Section: Soils As the Presumed Primary Source Of Brgdgts In Lake Sedimentioning
confidence: 99%